Evaluation of efficacy of photodynamic therapy as an adjunct to nonsurgical periodontal therapy in treatment of chronic periodontitis patients: A clinico-microbiological study - K Ravi Raj; SVVS Musalaiah; M Nagasri; P Aravind Kumar; P Indeevar Reddy; M Greeshma (Wolters Kluwer Medknow Publications, 2016)
Background and Objectives: Photodynamic therapy (PDT) is a local noninvasive treatment modality without side effects caused by antibiotics. The aim of this study was to evaluate the efficacy of adjunctive use of PDT with scaling and root planing as compared with SRP alone in the treatment of chronic periodontitis. Subjects and Methods: Twenty participants with chronic periodontitis having probing pocket depths (PDs) of ≥5 mm were selected for the study. Patients were randomly divided into control group and test group with ten patients in each group. Full-mouth SRP was performed in both the groups, followed by PDT in test group. Assessment of plaque index (PI), gingival index (GI), PD, and clinical attachment level (CAL) was done at baseline and after 3 months. Microbiological assessment of Porphyromonas gingivalis, Tannerella forsythia, and Treponema denticola was done by polymerase chain reaction (PCR) at baseline and 3 months after the therapy. Results: There was a significant reduction in PI, GI, PD, CAL, and microbiologic parameters in test group, following SRP and PDT, when compared with SRP alone in control group. Conclusion: PDT in conjunction with SRP has shown additional improvement in periodontal parameters when compared to SRP alone and has a beneficial effect in chronic periodontitis patients.